Characteristics of Patients Who Report Confusion After Reading Their Primary Care Clinic Notes Online. Issue 6 (2nd June 2016) - Root, Joseph; Oster, Natalia V.; L. Jackson, Sara; Mejilla, Roanne; Walker, Jan; Elmore, Joann G.
ABSTRACT: Patient access to online electronic medical records (EMRs) is increasing and may offer benefits to patients. However, the inherent complexity of medicine may cause confusion. We elucidate characteristics and health behaviors of patients who report confusion after reading their doctors' notes online. We analyzed data from 4, 528 patients in Boston, MA, central Pennsylvania, and Seattle, WA, who were granted online access to their primary care doctors' clinic notes and who viewed at least one note during the 1-year intervention. Three percent of patients reported confusion after reading their visit notes. These patients were more likely to be at least 70 years of age ( p  < .0001), have fewer years of education ( p  < .0017), be unemployed ( p  < .0001), have lower levels of self-reported health ( p  < .0043), and worry more after reading visit notes (relative risk [RR] 4.83; confidence interval [CI] 3.17, 7.36) compared to patients who were not confused. In adjusted analyses, they were less likely to report feeling more in control of their health (RR 0.42; CI 0.25, 0.71), remembering their care plan (RR 0.26; CI 0.17, 0.42), and understanding their medical conditions (RR 0.32; CI 0.19, 0.54) as a result of reading their doctors' notes compared to patients who were not confused. Patients who were confused by reading their doctors' notes were less likely to report benefits in health behaviors. Understanding this small subset of patients is a critical step in reducing gaps in provider–patient communication and in efforts to tailor educational approaches for patients.